Integrating market research and creative strategy: an advertising proposal for Stio - Zoller, Kaija, author; Slejko, Gina, advisor; Robinson, Arnold, committee member; Krukowski, Kipp, committee member (Colorado State University. Libraries, 2025)
This project integrates comprehensive market research with creative advertising strategy to develop an informed, multi-channel marketing proposal for Stio, a premium outdoor apparel brand rooted in mountain-athlete culture. Through industry analysis, competitive benchmarking, and consumer trend evaluation, the research identifies a rapidly evolving outdoor apparel landscape defined by rising participation in outdoor activities, growing demand for versatile and sustainable gear, and the increasing role of social media in shaping lifestyle-oriented outdoor fashion. Using quantitative and qualitative data, including onsite interviews, analytics, social listening, and third-party research, the project establishes four key consumer personas: the Graduated Grom, Mountain Maven, Eco Explorer, and Seasoned Seeker. These personas guide the development of a research-driven campaign concept, "The Gear That Does It All," which highlights Stio's ability to balance technical performance with everyday versatility. Paired with a six-month, funnel-based digital media plan spanning awareness, consideration, and conversion channels, the campaign is designed to support revenue growth, strengthen brand differentiation, and maintain Stio's aspirational mountain-towner identity. The resulting proposal positions Stio to expand its audience while preserving authenticity, addressing strategic challenges of credibility, brand dilution, and sustainability storytelling within a crowded and competitive market.
Marketing Department, Management Department.
Keywords: marketing; outdoor industry; advertising